Analysis of Youth Entrepreneurship Development in Facing Era 5.0 Using SAST Method - Novita Wahyu Setyawati; Dewi Sri Woelandari PG; Agus Dharmanto (PT FORMOSA CENDEKIA GLOBAL, 2022)
Youth entrepreneurship development with various challenges and potentials in entering the 5.0 revolution era. For this reason, in order to increase competitiveness, it becomes an impetus for Youth to improve their skills, knowledge, and analytical and leadership skills in the work environment. The purpose of this study was to determine the form of youth involvement and role in the Youth Entrepreneurship Program, to determine the driving and inhibiting factors faced by youth in providing their roles and participation in entrepreneurship programs, and to provide an overview of the level of adaptability among youth in the process of implementing youth entrepreneurship programs in terms of of mastery and utilization of technology. The method used is the SAST method. Strategic Assumption Surfacing And Testing (SAST) is a software method used to solve complex and interrelated problems, with unclear objectives, conflicts of interest, and environmental uncertainty and social constraints. From the results of the discussion and conclusions above, there are several steps that must be taken: Development of youth entrepreneurship, Synergy and cross-stakeholder collaboration in relevant ministries and institutions, Commitment to resource allocation, especially personnel/institutional and budget, as well as the National Action Plan Movement to purchase products. generated by young entrepreneurs.